Legal Analysis of Criminal Act of Rape Continues (Study of The Decision of The Surakarta District Court Number: 8/Pid.B/2024/Pn.Skt) - Arfina Manda Fransiska; Taufiq Nugroho; Indah Maulani (Proceeding International Conference Restructuring and Transforming Law, 2025)
Rape Rape is a form of sexual violence that is rampant in Indonesia. Rape is also an act that often occurs repeatedly so it is called ongoing rape. This crime is a concrete problem to be handled in the existing justice system. Punishment for rape often causes inequality for its victims because the existing punishment is considered disproportionate to the losses experienced by the victim. This paper qualitatively analyzes the judge's considerations and the application of punishment in the crime of ongoing rape based on the decision of the Surakarta District Court Number 8/Pid.B/2024/Pn.Skt. This paper applies the normative legal method with a case approach from the decision of the Surakarta District Court which shows that the judge's considerations are based on legal, philosophical, and sociological aspects. In the decision, the application of Article 285 and Article 64 paragraph (1) of the Criminal Code is relevant but the application of the threat of punishment is not optimal.